Synoptic analysis and forecasting : an introductory toolkit - Milrad, Shawn (Elsevier, 2025)
Synoptic Analysis and Forecasting: An Introductory Toolkit, Second Edition provides a bridge between early meteorology courses and more advanced courses in synoptic-dynamic analysis. This valuable reference also imparts qualitative weather analysis and forecasting tools and techniques to researchers and practitioners who require deeper foundational knowledge of weather forecasting. Sections introduce readers to surface weather instrumentation, observations, and plots, radiosondes and upper-air charts, a process-based guide to understanding the motion and intensity of cyclones, anticyclones, fronts, and the diagnosis of vertical motion and associated large-scale weather conditions. After learning about the applications of modern satellite and radar imagery to synoptic analysis and forecasting, readers are provided a complete three-dimensional picture of the troposphere through thermodynamic diagram and sounding analysis techniques. This invaluable resource offers strong support for building qualitative weather observation, analysis, and forecasting skills.